2014
DOI: 10.1007/s12571-014-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary contribution of Wild Edible Plants to women’s diets in the buffer zone around the Lama forest, Benin – an underutilized potential

Abstract: Rural populations in developing countries face food insecurity and malnutrition despite being surrounded by extraordinary biodiversity. The international community increasingly recognizes the role of agro-biodiversity and Wild Edible Plants (WEPs) in their contributions to managing risk and building resilience and sustainable food systems. Studies on real contributions of WEPs to peoples' diets, however, are uncommon. This study assessed the contribution of WEPs to diets of women living in the buffer zone of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 41 publications
5
58
4
3
Order By: Relevance
“…The findings in the present study corroborate the previous findings in DR Congo (12) , Benin (53) , Tanzania (57) , Ethiopia (69) and Cameroon (70) that indicated a wide gap between the number of traditionally known and the number of commonly consumed forest foods. The focus group respondents in the present study revealed a list of forty-seven forest plant foods, of which only seventeen were observed to be consumed during the 7 d recall period in the study.…”
Section: Knowledge Of Forest Foodssupporting
confidence: 92%
See 1 more Smart Citation
“…The findings in the present study corroborate the previous findings in DR Congo (12) , Benin (53) , Tanzania (57) , Ethiopia (69) and Cameroon (70) that indicated a wide gap between the number of traditionally known and the number of commonly consumed forest foods. The focus group respondents in the present study revealed a list of forty-seven forest plant foods, of which only seventeen were observed to be consumed during the 7 d recall period in the study.…”
Section: Knowledge Of Forest Foodssupporting
confidence: 92%
“…Research conducted with the Kisangani and Turumbu forest communities of DR Congo indicated that forest foods do not provide adequate intakes of the micronutrients Fe, Zn, Ca and vitamin B 12 , with less than 25% of women having intakes above the RDA (12) . The low contribution of forest foods towards meeting the EAR of these micronutrients has also been reported among the Lama Forest communities of Benin (53) . The lower nutrient contributions of forest foods in Benin (53) and DR Congo (12) than in the present study may be attributable to the exclusion of nutrient-rich animal foods.…”
Section: Contribution Of Forest Foods To Nutrient and Energy Intakesmentioning
confidence: 69%
“…Conservation studies in Cameroon reveal that non-respect of the wildlife legislation to protect wild life, has resulted in unsustainable hunting of wild animals for food (Cerutti and Tacconi, 2006;Nasi et al, 2011;Fungo, 2016). The major identified forest foods in Cameroon in the present study, are similar to studies reported in Cameroon and other Congo Basin countries (for example, Tacconi et al, 2003;Nasi et al, 2011;Termote et al, 2012;Hamawa, 2013;Boedecker et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are corroborated by case studies in DR Congo among the forest dependent communities of Kisangani (Termote et al, 2012), the Guiziga tribe in Cameroon (Hamawa, 2013) and populations adjoining Lama Forest reserve in Benin (Boedecker et al, 2014). Despite these communities having access to abundant nutrient rich traditional forest foods, under-nutrition and food insecurity is rampant among them.…”
Section: Introductionmentioning
confidence: 77%
“…Plusieurs études ont déjà montré l'importance des plantes sauvages dans l'alimentation et l'apport en micronutriments (Blaney et al, 2009 au Gabon ;Powell et al, 2013 en Tanzanie). Boedecker et al (2014) au Bénin observent que les femmes qui consomment des plantes sauvages ont une meilleure diversité alimentaire que celles qui n'en consomment pas. Ils soulignent que les plantes sauvages sont consommées en complément d'autres aliments plutôt qu'en substitution.…”
Section: Mai 2013unclassified